Minimal model of an active solid deviates from equilibrium mechanics - Sandoval, Mario (The European physical journal. B, Condensed matter physics, 2022)
In this work, the mechanical response of an one-dimensional active solid—defined as a network of active stochastic particles interacting by nonlinear hard springs— subject to an external deformation force, is numerically studied and rationalized with a minimal model. It is found that an active solid made of linear springs and subject to an external stress presents an average deformation which is independent of the system’s activity. However, when the active solid is made of nonlinear hard springs, the solid’s average deformation decreases with respect to a passive system under the same conditions, and as a function of activity and rotational noise in the system. The latter result may shed light on new ways to creating an active metamaterial, which could tune its stiffness by moving either its activity or rotational noise. Graphical abstract